Ecofisiologia, nutrição e análise econômica da palma forrageira sob diferentes manejos no semiárido brasileiro - Lopes, Marcos Neves (2016)
This study evaluated the water balance, chlorophyll-a fluorescence, nutritional status, accumulation and exportation of nutrients, nutritional efficiency, morphophysiological characteristics and economic viability of cactus pear cv. Gigante, fertilized with combinations of nitrogen (N) and phosphorus (P) at frequencies of annual and biannual harvests. The research was conducted in semiarid regions of Quixadá and Tejuçuoca, state of Ceará, Brazil, on nine combinations of N and P: five N levels (10; 70; 100; 130 and 190 kg ha-1 year-1) and five P2O5 levels (10; 70; 100; 130 and 190 kg ha-1 year-1), in a split-plot randomized block design with four replications (plots). The combined levels of nitrogen and phosphorus influenced the chlorophyll-a fluorescence, highlighting the PSII potential and effective quantum efficiencies and electron transport rate at different cladode orders, evaluated in dry and rainy periods, for the regions of Quixadá and Tejuçuoca. In Quixadá, for total forage biomass (TFB), in the annual harvest, we observed the maximum value (3522.9 kg ha-1 year-1) in the combination N/P2O5 of 134.6/190.0 kg ha-1 year-1. For TFB, in the biannual harvest, we observed the maximum value of 1583.2 kg ha-1 year-1 for the N/P2O5 combination of 114.6/136.8 kg ha-1 year-1. For rainfall use efficiency (RUE), in the annual harvest, we observed the maximum value (4.1 kg ha-1 mm-1) for N/P2O5 combination at 126.6/190.0 kg ha-1 year-1. For RUE, in the biannual harvest, we observed a maximum value of 4.1 kg ha-1 mm-1 for N/P2O5 combination of 114.6/136.8 kg ha-1 year-1. In Tejuçuoca, for TFB, in the annual harvest, the maximum value of 9783.0 kg ha-1 year-1 was verified for the N/P2O5 combination of 137.7/190.0 kg ha-1 year-1. For TFB, in the biannual harvest, we observed a higher value (12124.0 kg ha-1 year-1) for N/P2O5 combination at 190.0/56.8 kg ha-1 year-1. For RUE, in the annual harvest, we observed the maximum value (14.9 kg ha-1 mm-1) for N/P2O5 combination at 139.7/190.0 kg ha-1 year-1. For RUE, in the biannual harvest, we observed the maximum value of 19.9 kg ha-1 mm-1 for the N/P2O5 combination at 190.0/130.0 kg ha-1 year-1. In general, in both regions, the estimated contents of macro- and micronutrients at the levels for maximum production and 90% of the maximum are situated within the appropriate range, defined by balanced index of Kenworthy. In Quixadá, with annual harvest, we observed the following accumulation order of macronutrients: K > Ca > N > Mg > S > P. For micronutrients, the order was Mn > Fe > B > Zn. With the biannual harvest, for macronutrients, we registered Ca > K > S > N > Mg > P. For micronutrients, was verified Mn > Fe > B > Zn. In Tejuçuoca with annual harvest, for macronutrients, the order was K > Ca > N > Mg > S > P. For micronutrients, we found Mn > Fe > B > Zn. With the biannual harvest, for macronutrients, we verified K > N > S > Ca > Mg > P. For micronutrients, we observed Mn > Fe > B > Zn. The combinations of N and P influenced the nutritional efficiency indices in Quixadá and Tejuçuoca, in both frequencies of harvest. In Quixadá, the biannual harvest is the most recommended in the medium/long term, using the N/P2O5 combination of 114.6/136.8 kg ha-1 year-1. In Tejuçuoca, the N/P2O5 combination of 190.0/56.8 kg ha-1 year-1, under biannual harvest, maximizes the total forage biomass production. In Quixadá, the highest viability is achieved in the following conditions: annual harvest, with sale as seedling and N/P2O5 combination/Price of 173.4/190/0.25 and biannual harvest, with sale as seedling and N/P2O5 combination/Price of 184.9/190/0.25. In Tejuçuoca, the system has higher viability under the following situations: (I) annual harvest, with sale as seedling and fresh biomass and N/P2O5 combination/Price of 190/190/0.25; (II) biannual harvest, with sale as fresh biomass and N/P2O5 combination/Price of 190/136.5/0.10 and (III) biannual harvest, with sale as seedling and N/P2O5.